Permanent bilateral carotid filters for stroke prevention in atrial fibrillation - De Potter, Tom; Yodfat, Ofer; Shinar, Guy; Neta, Avraham; Reddy, Vivek Y.; Neuzil, Petr; Veltkamp, Roland; Connolly, Stuart J. (Current cardiology reports, 2020)
A novel permanent carotid filter device for percutaneous implantation was developed for the purpose of stroke prevention. In this review, we cover rationale, existing preclinical and clinical data, and potential future directions for research using such a device.